Tomb Architecture of the Chitral Valley, Pakistan - Shakirullah (Ancient Pakistan, 2021)
Chitral is located in the north-western part of the Khyber Pakhtunkhwa province, Pakistan (Dani, 2007, 12-13), between 71° 12’ and 73° 53’ east longitude and between 35° 13’ and 36° 55’ north latitude, bounded on the north and west with Afghanistan and on the east and south with Northern areas and Dir and Swat districts of Khyber Pakhtunkhwa province (Cacopardo, 2001, 45-46). Culturally and physically, Chitral valley is the most isolated region of Pakistan (Dichter 1967: 24-26). Tomb architecture of the Chitral valley forms a separate group. For the development of architecture some basic requirements such as wealth, political peace and good environment are very essential. Till the last quarter of the 19th century, Chitral had none of these. In 1313 H/AD 1895 (Aziz, 1991, 208) the British army of India cleaned the area from terrorists / local warriors and appointed Shujā΄ ul–Mulk as Mihtar of Chitral on September 2 (1895). With this the Sunnis, Shi΄as, Isma΄īlies and Nūrbakhshi sects (Jettmar, 1992, 13) integrated with each other. That is why we find religious buildings such as mosques and tombs not earlier than the 19th century AD (Shakir, 2012, 20). Three types of structures are noteworthy with reference to their building material: (1) mud with stones, (2) mud with wooden courses and (3) wooden structures.